Forty years of Landscape Research. (18th May 2016) - Vicenzotti, Vera; Jorgensen, Anna; Qviström, Mattias; Swaffield, Simon
Abstract: Papers of four decades published in Landscape Research are reviewed in order to chronicle the journal's development and to assess the academic performance of the journal relative to its own aims . Landscape Research intends to reach a wide audience, to have a broad thematic coverage and to publish different types of papers with various methodological orientations. Cutting across these first aims are the interdisciplinary ambition of the journal, and its overall focus on landscape. These aims are evaluated based upon categorisation of article content, authorship and methodology, using data derived through interpretative inquiry and quantitative analyses. The results tell the story of how Landscape Research has developed from a newsletter of the Landscape Research Group, mainly aimed at practitioners, into an interdisciplinary, international journal with academic researchers as its primary community of interest. The final section discusses the current profile of the journal and identifies issues for its future direction and development.